Taylor Landry: capstone - Landry, Taylor, artist (Colorado State University. Libraries, 2017)
The artist's statement: Often, I find myself stopped in the street, observing how perfectly composed the caution tape floating in a leaf strewn puddle over a break in the curb appears. What conspired for everything to come together in this exact moment? Chance happenings and the passing of time effortlessly arrange materials around me into complex compositions that inform my work. The splatters, scratches, and scattered debris silently decorating my environment inspire how I use dye, stitch, and found objects. The act of weaving individual threads into a unified cloth serves as a metaphor for how the tapestry of what makes us human is woven together with endless interconnecting strands of memory, emotion, relationships, and experiences. I weave to illuminate small moments and observations. I embroider found object collages and instant photographs of my everyday surroundings as a way to stitch together the untold narrative with the obvious and tangible and to delight in the random arrangement of our universe. Music and lyrics fuel my soul in a way that no other thing can, a thread so permanently entwined in the cloth of my own identity, fundamentally altering the way I perceive the world. For this body of work, I chose to honor the music that has impacted my identity most by composing titles inspired from song lyrics by the band, Modest Mouse. Provoked by my observations of the growing and decaying world around me, sparked by the fascination of how all things come together, and fueled by the words, sounds, and textures that fill my space, I construct in needle and thread a diary of my experience and identity. I expand and evolve small fragments of my surroundings to invoke the whole - landscapes of humanity.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: fibers; fiber art; mixed media; collage; weaving; embroidery; fiber concentration; fiber; natural dyes; textile art